Women Producers of Kiribati and Their Participation in Inter-Island and International Trade - United Nations Conference on Trade; Development (United Nations, 2021)
This report investigates the income-generating activities of women producers and traders in Kiribati and the constraints they face in production and trade activities. Research was conducted in the four islands of South Tarawa and Kiritimati as urban areas, and Arorae and Making as rural areas. Kiribati’s fragmented geographic structure and limited connectivity, narrow range of resources, high dependence on imports, and lack of economies scale – all of which are common to most small island developing States – create challenges for the expansion of the private sector and inter-island and international trade. Remoteness results in slower penetration of modern technologies and poses challenges for imports of raw materials and intermediate goods unavailable domestically. Weak business infrastructure, limited access to finance and burdensome licensing and trade procedures imply additional costs, inhibiting the development of the private sector. Policy recommendations are included that could help address the country's constraints.